Analisis Peran OJK Dalam Menjamin Penegakan Hukum Perusahaab Pegadaian Swasta Non-Bank - Oktania, Ainur; Dwi Silfani; Ferozi Ramdana Irsyad; Bonaraja Purba (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The rapid growth of private non-bank pawnshops in Indonesia poses challenges in maintaining financial stability and consumer protection. The Financial Services Authority (OJK) plays a role in ensuring that pawnshop business activities are conducted in accordance with the law. This study aims to analyze the role of the OJK in supervising and enforcing the law against private non-bank pawnshops, as well as the challenges in its implementation. The method used is a qualitative approach through literature review. The results of the study indicate that the OJK conducts preventive supervision through socialization, detective supervision through inspections, and repressive supervision in the form of administrative sanctions. However, the effectiveness of supervision is still hindered by limited human resources, weak criminal sanction authority, and low legal literacy among the public. As a result, there is a need to strengthen regulations, improve human resource capacity, and foster inter-agency collaboration and public education to create legal and safe pawnbroking businesses.